Impacto sistêmico dos tratamentos da periodontite e da periodontite apical em ratos obesos e não obesos - Pintos, Cynthia Mireya Jara (2020)
Both obesity and the main chronic oral diseases - periodontitis (PE) and apical periodontitis (AP) - share a chronic, long-lasting, low-intensity inflammatory nature. The increase in serum levels of inflammatory mediators has been associated with an increased risk of the development and progression of several chronic non-communicable diseases. The systemic repercussions of the presence of PE and AP, as well as the possible influence of endodontic and periodontal treatment on the levels of systemic inflammatory mediators in obese and non-obese individuals, are still not fully understood. This thesis consists of 4 articles, the first two of which are methodological in nature, and the next two are dedicated to assessing the systemic effect of oral lesions and their treatments. Thus, the articles that make up this thesis have the following objectives:: 1- evaluate the accuracy of electronic foramen locators in rats; 2- evaluate the feasibility of two experimental models for the treatment of AP in rats; 3- to evaluate the impact of the treatment of AP and PE on the serum levels of inflammatory mediators and metabolic profile in obese and non-obese rats and 4- to evaluate the impact of the treatment of AP and PE on the aorta and liver of obese and non-obese rats. Methods: In article 1, pulp exposure was performed in the mesial fossa of the lower first molar of 24 three-month-old Wistar rats, weighing 230-250 grams. The Mini Apex Locator (SybronEndo) was connected to a file # 10 and introduced until reaching the apical foramen, then it was measured. The radiographic and electronic working length was compared and analyzed using Pearson's Correlation Coefficient. In article 2, 18 three-month-old Wistar rats and weighing 230-250 grams were used. AP was induced in 15 animals over a period of four weeks. The animals were divided into four groups: G1 canal treatment / rhizhectomy, G2 extraction, G3 PA without treatment, G4 without PA. Four weeks after treatment, euthanasia was performed and radiographic repair was evaluated. In articles 3 and 4, 140 Wistar rats, three months old and weighing 250-300 grams, were used and divided into two large groups differentiated by the diet administered: standard diet, without obesity (-n) and cafeteria diet, with induced obesity (-c). These groups, in turn, were distributed in seven subgroups with ten animals each, according to the following experimental protocols: control rats with no injury (NI); rats with induced AP (AP); rats with induced and treated AP (APt); rats with induced PE (PE); rats with induced and treated PE (PEt); rats with induced AP and PE (APPE); and rats with induced and treated AP and PE (APPEt). AP and PE injuries were induced for a period of four weeks. After four weeks of AP and PE treatments, the animals were euthanized and the serum levels of the inflammatory mediators IL-10, IL-6, IL-1β, TNF-α and IL-17a were measured, as well as the levels of cholesterol, glucose and triglycerides (article 3). The aorta and liver were dissected for histological evaluation (article 4). The data were tabulated and analyzed using descriptive statistics. Differences between groups were analyzed using the Kruskal-Wallis tests and logistic regression. Results: In article 1, the results revealed a strong correlation between the electronic and radiographic length measurement (r = 0.912; p <0.05). In article 2, in G1, an incomplete removal of the medial and distal roots was observed. G2 showed good bone repair after extractions. In article 3, with respect to the metabolic profile, triglyceride levels were the most affected by the diet, showing a significant increase in all groups -c in relation to groups -n. Regarding glucose, the only higher and statistically significant value was APPEt-c when compared to NI-n. Among the inflammatory markers, no significant differences were found in the concentration of IL-6, IL-1β and TNF-α between the groups. IL-10 showed a significant increase in the APt-n and APt-c groups in relation to the NI-n group, and the APt-c group in relation to the NI-c group. In IL-17a a significant increase was observed in the APt-n, APt-c and APPEt-c groups in relation to the NI-n group. A tendency of elevation of the cytokines was observed independent of the diet administered. In article 4, the thickness of the aorta was statistically higher (p <0.05) in the APPEt-c group compared with four other groups; NI-n, APt-n, APt-c and AP-c. Regarding aortic alterations, the logistic regression model was statistically significant (p = 0.002). Compared with control groups, untreated groups were 7.7 times more likely to have alterations in endothelial cells (OR=7.7; 95%CI=2.4-25) and treated groups 2.9 (OR=2.9; 95%CI=1.0-8.4). The diet did not significantly influence (p = 0.174) the endothelial parameters analyzed in the aorta. In the liver analyzes, the logistic regression model was statistically significant (p <0.001), but of the predictor variables, only the diet was statistically significant (OR = 0.049; 95% CI = 0.009-0.260), where obese rats demonstrated greater changes of alterations on liver parameters compared to non-obese rats. Conclusion: Article 1 showed that the Electronic Foramen Locator is a precise method to perform the conductometry in rats. Article 2 showed that extraction could be a more predictable treatment for treating AP in rats. Observing articles 3 and 4, in general, it could be perceived the influence of oral lesions on the blood and tissues studied. However, in the study model used for this study, the treatment of AP and PE only improve the systemic conditions in one of the parameters. Article 3 suggested that regardless of the diet administered, serum levels of inflammatory mediators and cholesterol underwent an increase in the presence of AP and PE, with significant increases in the treated groups. However, in article 4, AP and PE were associated with the development of histological alterations in the aortic arch of Wistar rats. Despite the treatments of AP and PE have not changed the aorta thickness, it was revealed to reduce the vascular endothelial lesions. In addition, there was a non-significant trend of increased liver steatosis in the combination of AP and PE.